PERCEPTIONS AND ATTITUDES OF UPPER MYANMAR STUDENTS AND PARENTS TOWARDS ONLINE LEARNING: A CASE STUDY OF AN INTERNATIONAL SCHOOL IN MANDALAY DURING THE COVID-19 PANDEMIC - Garton, Michael; Cleesuntorn, Athipat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The aim of this study was to analyse and compare students’ and parents’ perceptions and attitudes towards online learning. The research took place at an international school in Mandalay, currently undergoing a period of online learning due to the Covid-19 pandemic. A seeming widespread disinclination towards this form of instruction lead to a focus on perceptions and attitudes and use of the Technology Acceptance Model. The reason for comparing the generations was to determine whether students, ‘digital natives’, would take more readily to online learning than their ‘digital immigrant’ parents, often deemed members of a ‘missing generation’ in Myanmar. Data and opinions were collected via electronic questionnaires from a total of 305 participants and examined using statistical analysis software. Multiple Linear Regression analyses were carried out to determine the influence of the independent variables, perceived ease of use and perceived usefulness, on attitude in both generations. A t-test was also conducted to compare values between generations. Perceived ease of use and perceived usefulness were shown to be good predictors for attitude in both generations, confirming results of earlier studies. No significant variances could be found in students’ and parents’ attitudes. However, there was a statistically significant difference for perceived usefulness, which contradicted the assumption that students would see more value in online learning than their parents. Opinions provided additional contextual data and highlighted several overriding concerns. Future research should widen the scope and examine actual use and effectiveness of online learning tools.